"Homeless Killer": An Analysis of the Media's Portrayal of the Victims of a Serial Killer. Issue 2 (1st February 2017) - Donley, Amy M.; Gualtieri, Marie C.
ABSTRACT: Previous research has examined the newsworthiness of homicide victims and explored many characteristics of victims. To date, there is no research examining homeless homicide victims even though homeless individuals are more susceptible to being victims of violent crimes. This study examines the online media coverage of four homeless homicide victims murdered by a serial killer in 2012 to ascertain how housing status impacts media coverage. Specifically, this study explores through content analysis what kind of coverage homeless individuals receive and how they are portrayed. Findings suggest that housing status is a salient characteristic in the newsworthiness of victims.